Gender-Based Health Disorders in End-Stage Renal Disease Patients in the Hospital Elmarj City of Libya - Astuti, Ari Yuni; Amkhatirah, Emad Mousay Mohammed (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
End-stage renal disease is the last stage of chronic kidney disease, hence a dangerous disease and poses many problems for the patients. The aim of this study was to analyze the risk factors for end-stage renal disease in Elmarj, Libya. Data was collected by distributing questionnaires to the respondents. The questionnaire was a set of written questions used to obtain information from respondents, be it their personal statements or things that they knew. The questionnaires were distributed to the respondents in person; the researchers distributed questionnaires to the respondents. The aim of this research is to determine the risk factors associated with ESRD (hypertension, DM, urinary tract infection, urinary tract stone, and obesity) among patients with ESRD the hospital Elmarj City Libya. This can be seen as the descriptive risk factors.